Reconstruction of the Inheritance of Cryptocurrency Assets in the Civil Code: A Review of the Saisine Principle and the Valuation of the Legitimate Portion - Nurul Ramadhani Razak (Civiliza Publishing, 2026)
The advancement of blockchain technology and the Web3 ecosystem has generated new forms of wealth in the shape of digital assets (such as cryptocurrencies and NFTs), creating a conceptual dissonance within Indonesia’s civil inheritance law framework. The legal vacuum concerning the status of decentralized cryptographic assets controlled by private keys has resulted in obstacles to the implementation of the saisine principle (the automatic transfer of rights by operation of law), while simultaneously giving rise to appraisal challenges in determining the legitime portie (forced heirship portion) due to extreme price volatility. This research aims to reconstruct the modern concept of proprietary control in relation to the saisine principle and to formulate equitable mechanisms for the execution and valuation of digital assets for heirs. The method employed is normative legal research using statutory, conceptual, and analytical approaches. The findings conclude that: (1) cryptographic access rights (private keys) must be juridically recognized as an inherent part of intangible movable property. The implementation of the saisine principle in relation to crypto assets requires ex-ante mitigation through Digital Wills, the institutionalization of smart contracts as executors of testamentary intent, and the adoption of multi-signature wallets and Shamir Backup methods; (2) the fulfillment of the legitime portie necessitates a paradigm shift from fiat-based appraisal toward in-natura distribution (token-based appraisal) by applying the Shared Volatility Risk Principle. This adjustment in valuation methods demonstrates the hermeneutic flexibility of the Civil Code in preventing inheritance disputes while safeguarding the civil rights of heirs in the era of digital transformation.